Pemanfaatan Tumbuhan Liar Bandotan (Ageratum conyzoides L.) sebagai Obat Tradisional dan Aktivitas Farmakologinya - Raudatul Hilaliyah (Universitas Lambung Mangkurat, 2021)
Bandotan (Ageratum conyzoides L.) is a plant belonging to the Asteracea family. This plant is widely used as medicine in various countries such as Africa, Asia and South America. Bandotan is used as medicine because it contains useful phytochemical compounds such as terpenoids, alkaloids, essential oils, saponins and phenolics. Some of the pharmalogical activities on bandotan include antibacterial, anti-inflammatory, antioxidant, and antidiabetic. Several studies have shown that bandotan can be used as a treatment for fever, rheumatism, headaches, stomach aches, medicine for pneumonia, drugs for diarhea, diabetes, and HIV/AIDS. The article review is expected to provide information about the use of bandotan as a traditional medicine or herbal medicine and its pharmacological activity.